Evaluation of Cytotoxic Activity of Sargassum vulgare From the Lebanese Coast Against Jurkat Cancer Cell Line - Mona Y. Tannourya, Josiane M. Eliaa , Antoine M. Saabc, Hassane Y. Makhloufb, Jihad S. Abboudd, Roula J. DaouChaboa, Mona Diab-Assafb (Journal of Applied Pharmaceutical Science, 2016)
The discovery of cancer drugs that effectively destroy cancer cells or stop their growth without toxicity to normal cells is a challenge to enhance the therapeutic effects and reduce side effects. Many papers have highlighted the implication of marine algae that show anticancer activity. In this report, we assessed the cytotoxic activity of two different crude extracts from Sargassum vulgare (Sargassaceae), a marine brown algae collected from the Lebanese coast, against Jurkat human cancer cell line using trypan blue exclusion test. Both extracts, water: ethanol extract and chloroform: ethanol extract, showed cytotoxic activity against Jurkat cancer cell line with IC50 values of 136.907 µg/ mL and 49.056 µg/ mL, respectively after 72 hours of treatment. Further research designed to isolate and identify novel and efficient anticancer drug candidates from these seaweed extracts need to be explored.